Electromagnetic force compensation weighing cell with magnetic springs and air bearings. (28th October 2020) - Yoon, Kyung-Taek; Park, Sung-Ryong; Choi, Young-Man
Abstract: The electromagnetic force compensation (EMFC) principle is a state-of-the-art weighing method for precision mass measurement. In this method, the low stiffness of the flexure-based Roberval guide mechanism and high lever ratio of force transmission contribute to achieving extremely high weighing sensitivity. However, weak damping and the parasitic resonant frequencies of the flexure mechanism lead to a slow settling time after loading a weight. Moreover, the low ruggedness of the flexure mechanism limits the load capacity of the EMFC weighing cell and may result in fatigue failure under repeated loading. In this paper, we propose a novel precision weighing cell with Halbach array magnetic springs and air bearings instead of the flexure mechanism. The magnetic spring is designed for near-zero negative stiffness to increase the system bandwidth, as well as for gravity force compensation ability against deadweights. The air bearings ensure high ruggedness toward parasitic directions with high stiffness in the parasitic direction and a damping effect from the pressurized air film. The stiffness of the fabricated prototype weighing cell is −27.3 N m −1, which is tens of times lower than that of conventional EMFC weighing cells. The weighing repeatability of the weighing cell is 2.35 mg, as measured with a 10 g E2 class test mass, and the settling time within ±2% of its final value is 57 ms in air.